MENGGAGAS KINERJA BIROKRASI PUBLIK - Teguh Yuwono (Badan Kepegawaian Negara | The National Civil Service Agency, 2008)
Change in the public sector is the rule rather than the expectation. The quest for the perfect way of structuring and managing government has gone on as long as there has been a government, always to end in disappointment. The problem has been in part that no single definition of what constitutes perfect administration exists. Further, each solution tends to create its own new set of problems, which in turn will create a new set of reforms. Although this cycle of reform is beneficial for those of us interested in the process of change, it is less so far for those involved in the process. Frequent changes tend to create cynicism about reform efforts both inside and outside the public sector. However, such efforts can be a politician’s best friend, given that they are at times the only possible reaction to intractable policy problems